Konten Dakwah dalam Youtube Pesulap Merah Production - Muchammad Fadlan (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
In the digital era, when the Internet is getting cheaper and easier to access, people’s interaction with the digital world is increasing. One of them is access to YouTube content, with various purposes, one of which is entertainment content with magic as the material. Pesulap Merah Production is one of these YouTube channels. More interestingly, the channel combines entertainment and Da’wa. This research emphasizes how Pesulap Merah carries out the Da’wa content by analyzing the YouTube content of Pesulap Merah Production. In the research results, Da’wa inserts in the content of Pesulap Merah are considered more appealing and acceptable to viewers amid various sensitive issues related to faith issues and social problems in society. With 3.2 million subscribers and an average of 200 thousand viewers, social changes that occur in society are one indicator of the success of this Da’wa